2012
DOI: 10.4236/health.2012.412a200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in men and women with upper or lower types of body fat distribution

Abstract: The purpose of the study was to determine the prevalence of metabolic syndrome as a cluster of risk factors for atherosclerotic cardiovascular disease and type 2 diabetes mellitus and its individual components in groups of men and women with primary obesity having different types of fat distribution. The study involved 142 men and 185 women with primary alimentary-constitutional obesity. The study participants were divided into 2 groups depending on waist-to-hip ratio value. Standardized criteria were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(59 reference statements)
0
7
0
7
Order By: Relevance
“…Нами показано, что АТРЖ и ГТРЖ ассоциированы с различным риском развития метаболического синдрома (МС): частота МС при ГТРЖ у женщин ниже в 1,9 раза, а у мужчин -в 2,7 раза, чем при АТРЖ [16]. И у мужчин, и у женщин в группах с ГТРЖ отсутствовал такой компонент МС, как гипергликемия, т.е.…”
unclassified
“…Нами показано, что АТРЖ и ГТРЖ ассоциированы с различным риском развития метаболического синдрома (МС): частота МС при ГТРЖ у женщин ниже в 1,9 раза, а у мужчин -в 2,7 раза, чем при АТРЖ [16]. И у мужчин, и у женщин в группах с ГТРЖ отсутствовал такой компонент МС, как гипергликемия, т.е.…”
unclassified
“…We have previously shown that abdominal (upper) obesity has more pronounced negative effects on human health than gynoid (lower) obesity [23], not only in women but also in men. The upper type of fat distribution is associated with intra-abdominal visceral fat accumulation, which plays an important role in the development of diabetes, lipid disorder, hypertension and atherosclerosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of bright light in the treatment of obesity in men needs further investigation. Gender differences probably would be determined not so much the severity of obesity, but the specialty of the fat depots topography, which have significant differences in men and women [58].…”
Section: Discussionmentioning
confidence: 99%